Enzyme Specific Drug Delivery System: A Potential Approach for Colon Targeting - Soni, P; Chaudhary, GP; Soni, LK (Current Research in Pharmaceutical Sciences, 2015)
Although oral delivery has become a widely accepted route of administration of therapeutic drugs, the gastrointestinal tract presents several formidable barriers to drug delivery. Colonic drug delivery has gained increased importance not just for the delivery of the drugs for the treatment of local diseases associated with the colon but also for its potential for the delivery of proteins and peptides. To achieve successful colonic delivery, a drug needs to be protected from absorption or the environment of the upper gastrointestinal tract (git) and then be abruptly released into the proximal colon, which is considered the optimum site for colon-targeted delivery of drugs. Peptides, proteins, oligonucleotides and vaccines pose potential candidature for colon targeted drug delivery. The various strategies for targeting orally administered drugs to the colon include covalent linkage of a drug with a carrier, coating with pH-sensitive polymers, formulation of timed released systems, exploitation of carriers that are degraded specifically by colonic bacteria, bioadhesive systems and osmotic controlled drug delivery system. Certain plant polysaccharides such as amylose, inulin, pectin and guar gum remains unaffected in the presence of gastrointestinal enzymes and pave the way for the formulation of colon targeted drug delivery systems. Natural polysaccharides have been used as tools to deliver the drugs specifically to the colon. These polysaccharides remain intact in the physiological environment of stomach and small intestine but once the dosage form enters into colon, it is acted upon by polysaccharidases, which degrades the polysaccharide and releases the drug into the vicinity of bioenvironment of colon. However, they should be protected while gaining entry into stomach and small intestine due to enormous swelling and hydrophilic properties of polysaccharides. This has been achieved either by chemical crosslinking or by addition of a protective coat. The advantages of targeting drugs specifically to the diseased colon are reduced incidence of systemic side effects, lower dose of drug, supply of the drug to the biophase only when it is required and maintenance of the drug in its intact form as close as possible to the target site.